The Patient as Genomic Data Manager - Evaluation of the PROMISE App - Griebel, Lena; Hinderer, Marc; Amr, Ali; Meder, Benjamin; Schweig, Marc; Deuber, Dominic; Egger, Christoph; Kawohl, Claudia; Krämer, Annika; Flade, Isabell; Schröder, Dominique; Prokosch, Hans-Ulrich (Digital Personalized Health and Medicine, 2020)
PROMISE (Personal Medical Safe) was a German research project which aimed to provide the responsibility of genomic data to the patient via a mobile app. The patient should accept or decline study requests to use his/her genomic data via the app. In the evaluation of the app the experiences with mobile health as well as the opinion on being the genomic data manager were measured. Furthermore, the test patients were asked about their opinion and their concerns on the PROMISE app. Most of the 19 test patients were aware of the high sensibility of genomic data and thought that the PROMISE app was a suitable solution. The largest part found it good that they were the responsible data owner. However, several participants also found it important to have a permanent contact person when it comes to questions on inquiries or the app.
CRIS-Team Scopus Importer:2020-07-03
Keywords: genomic sequencing; patient empowerment; Personalized medicine; technology acceptance